A facile assembly of 3D robust double network graphene/polyacrylamide architectures via γ-ray irradiation. (8th February 2016) - Zhu, Ting; Teng, Kunyue; Shi, Jie; Chen, Lei; Xu, Zhiwei
Abstract: Addressed herein was a facile one-step method to obtain three-dimensional (3D) robust double network graphene/polyacrylamide architecture (DNGA) which was constructed by polyacrylamide-modified graphene network and polyacrylamide (PAM) network via γ-ray irradiation. The application of γ-ray irradiation technique promoted the efficient preparation of 3D graphene networks for its characteristic of high energy. The resultant DNGA with an ordered double network macroporous structure achieved high compressive strength of 1.45 MPa, which was quadruple compared with that in previous reports. After being thermal-annealed at 800 °C in N2 atmosphere, the obtained DNGA/N2 with stable porous structure exhibited an excellent Young's modulus of 2.93 MPa, which was triple higher than that reported in the latest literature. Considering the outstanding compressive property of DNGA and DNGA/N2, a series of analyses supported the strengthening mechanism of the double network. The present results suggest that the convenient synthetic approach can act as a potential candidate for fabricating high-strength 3D graphene materials, which may provide insight into a meaningful development of large-scale and low-cost preparation of 3D graphene networks.